Fractionated organic carbon in relation to soil aggregates and other soil properties in humid, tropical lowland, salt-affected soils - Boonrit, Kanokpon; Anusontpornperm, Somchai; Thanachit, Suphicha; Jindaluang, Wittaya (Agriculture and Natural Resources, 2024)
Importance of the work: The understanding of the relationships among soil properties, soil aggregates, and fractionated organic carbon (OC) in tropical, lowland, salt-affected soils (SASs) is unclear and requires further investigation. Objectives: To investigate the proportion of OC fractions in relation to water stable aggregates (WSAs) and other soil properties in selected SASs. Materials & Methods: Lalerng Phimarn and Non Thai transects were chosen with four soils along each toposequence (LP1–LP4 and NT1–NT4, respectively). Fractionated OC, WSAs and other soil properties were analyzed. Results: All SASs were classified as Typic Natraqualfs with silt+clay and with sand particles dominating in the soils of the LP and NT transects, respectively. Only aggregates < 0.50 mm were detected in these SASs. Dissolved OC was almost undetectable. Particulate organic matter was positively and negatively correlated with the sand (r = 0.783, p < 0.01) and clay (r = -0.812, p < 0.01) contents, respectively. This fraction was adversely affected by electrical conductivity (r =-0.706, p < 0.01) and the sodium adsorption ratio (r = -0.741, p < 0.01). The OC bound to silt+clay increased with increasing WSA5 (0.1–<0.25 mm; r = 0.542, p < 0.015) and mean weight diameter (r = 0.525, p < 0.01) and was positively correlated with OM (0.650, p < 0.01), total N (r = 0.544, p < 0.05) and extractable Ca (r = 0.526, p < 0.05). The chemically resistant OC had a positive correlation with WSA7 (< 0.053 mm; r = 0.686, p < 0.01) and clay content (r = 0.581, p < 0.05). Main finding: Sodium overcame OM and induced WSA breakdown in these SASs. The s+c dominated, while the particulate OM was equally dominant in the sandier SASs. The chemically resistant carbon fraction was vital for C sequestration in the SAS subsoil.